PENGARUH PEMBERIAN BIOCAR TERHADAP TANAMAN KANGKUNG DARAT DI LAHAN TERCEMAR LIMBAH CAIR (DI SUBAK CUCULANDESA KEPAON) - Murjaya, I Made; Sujana, Putu; Suryana, Made (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
The research aims to determine the type of biochar that is best used for the growth and yield of kangkungdarat plants grown on land contaminated with liquid waste. The study used a Randomized Block Design (RBD) using 5 treatments, using the treatment of rice husk biochar (B1), chicken manure biochar (B2), coconut shell biochar (B3), mahogany biochar (B4) and control (B0). The treatment of chicken manure biochar (B2) showed significantly different results (P <0.01) compared to the control (B0) of all observational parameters such as maximum plant height per plant, maximum number of leaves per plant, total wet weight of plants per plant, plant root wet weight per plant, total plant dry weight per plant and dry weight of plant roots per plant. The results of the study showed that the supply of chicken manure biochar (B2) at a dose of 15 tons / ha could increase plant height, leaf number, plant total wet weight, root wet weight plants, total dry weight of plants and dry weight of root water spinach plants.